3′, 4′-Dihydro-2′H-spiro[indoline-3, 1′-isoquinolin]-2-ones as potential anti-cancer agents: synthesis and preliminary screening. Issue 1 (8th January 2020) - Lobe, Maloba M. M.; Efange, Simon M. N.
Abstract : Both tetrahydroisoquinolines (THIQs) and oxindoles (OXs) display a broad range of biological activities including anti-cancer activity, and are therefore recognized as two privileged scaffolds in drug discovery. In the present study, 24 3′, 4′-dihydro-2′H-spiro[indoline-3, 1′-isoquinolin]-2-ones, designed as molecular hybrids of THIQ and OX, were synthesized and screened in vitro against 59 cell lines in the NCI-60 screen. Twenty compounds displayed weak to moderate inhibition of cell proliferation; among them, three compounds displayed at least 50% inhibition of cell proliferation. The compounds appeared to target primarily renal cell cancer lines; however, leukaemia, melanoma, non-small cell lung cancer, prostate, ovarian and even breast cancer cell lines were also affected. Therefore, this class of spirooxindoles may provide useful leads in the search for new anti-cancer agents.